Self-Emulsifying Drug Delivery Systems: A Review - Reza, Jamilur (International Journal of Pharmaceutical and Life Sciences, 2013)
Self-emulsifying drug delivery systems (SEDDS) possess unparalleled potential in improving oral bioavailability of poorly water-soluble or lipophilic drugs. Following their oral administration, these systems rapidly disperse in gastrointestinal fluids, yielding micro- or nanoemulsions containing the solubilized drug. Owing to its miniscule globule size, the micro/nanoemulsified drug can easily be absorbed through lymphatic pathways, bypassing the hepatic first-pass effect. But it has drawbacks as formulation development, quality control, stability etc. These liquid SEDDS can be converted into solid dosage form without affecting drug release property. After administering the drug gets released and self emulsify in the GI tract. Generally solid SEDDS are formed with mono, di or triglycrides of fatty acid, non ionic surfactants and solidifying agents with diluents such as microcrystalline cellulose, lactose etc. DOI: http://dx.doi.org/10.3329/ijpls.v2i2.15453 International Journal of Pharmaceutical and Life Sciences Vol.2(2) 2013: 80-84